2022
DOI: 10.3390/ijerph19148633
|View full text |Cite
|
Sign up to set email alerts
|

Static Foot Disturbances and the Quality of Life of Older Person with Rheumatoid Arthritis

Abstract: Disturbed static foot function is one of the main causes of impaired quality of life, which may be related to the frailty syndrome of older adult patients with Rheumatoid Arthitis (RA). The aim of the study was to evaluate the relationship between parameters of static foot function disturbances and quality of life of older adult patients with RA. The study was performed among 102 patients with RA diagnosed according to the American College of Rheumatology (ACR) and EULAR 2010 criteria. Patients were divided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Katarzyna et al examined the relationship between static foot dysfunction assessed by plantoconturography and quality of life in 102 elderly patients with RA in remission. They found a relationship between static foot dysfunction and physical activity domain and emotional domain of quality of life in patients with RA [26]. Based on this result, we see that foot/ankle problems affect the psychosocial parameters of the person, and we think how important and necessary are the intervention methods for foot/ankle problems.…”
Section: Stolt Et Al (2017)mentioning
confidence: 66%
“…Katarzyna et al examined the relationship between static foot dysfunction assessed by plantoconturography and quality of life in 102 elderly patients with RA in remission. They found a relationship between static foot dysfunction and physical activity domain and emotional domain of quality of life in patients with RA [26]. Based on this result, we see that foot/ankle problems affect the psychosocial parameters of the person, and we think how important and necessary are the intervention methods for foot/ankle problems.…”
Section: Stolt Et Al (2017)mentioning
confidence: 66%
“…(3) This technique considers ratios( 0.50 _ 0.70) to be normal, whereas ratios over 0.70 to be pes planus [31] Wejsflog's index: which is the foot length to foot width ratio, is used to diagnose transverse flatfoot [32][33][34]. The value of this index remains between 2 and 3, and transverse flatfoot may be identified when it is closer to 2, while it is normal when it is closer to 3 [32][33][34]. it is recommended that assessment of foot posture.…”
Section: Methodsmentioning
confidence: 99%
“…Functional foot problems affect about 10-24% of the population, and this prevalence increases in patients with RA. Williams et al [10] report that most RA patients complain of a foot problem even before the disease is diagnosed. Measures to address the problems known as rheumatoid foot have been the subject of many studies.…”
Section: Occurrence Of Flat Feetmentioning
confidence: 99%
“…According to a study Kaniewska et al [10] conducted on 102 patients with RA, involving static assessment of the feet using a podoscope, a correlation was established between foot deformities and quality of life. The study showed that static foot abnormalities had a significant impact on all areas of quality of life.…”
Section: Examination Using a Podometermentioning
confidence: 99%